Archaeology of the Late Local Landscapes of the Hualfín Valley (Catamarca, Argentina): A Political Perspective from Cerro Colorado of la Ciénaga de Abajo - Wynveldt, Federico (2023)
As seen in many examples of imperial expansions throughout history, the Inkas applied a whole range of policies strategically adapted for the different local organizations, in every corner of their empire, and local groups, in turn, were reconfigured based on the new conditions. Starting from the investigation of a group of late local landscapes of the Hualfín Valley (Department of Belén, Catamarca) in the Northwestern Argentina, from a critical perspective of the sociopolitical definitions classically given to these societies, the aim of this study consists of describing the spatial, social, and temporal dimensions of these landscapes and advancing the discussion about how local groups socially and politically organized themselves, in immediately pre-Inka times and after the incorporation of their territories into the Inka state. To this end, a brief discussion on the Late and Inka periods in Northwestern Argentina and theoretical guidelines for landscape analysis are presented. Then, we address the analysis of one of the landscapes in particular: the Cerro Colorado de La Ciénaga de Abajo and its surroundings, and we briefly analyze the cases of Asampay, Palo Blanco, and Puerta de Corral Quemado, and the regional landscape network.